1992
DOI: 10.1097/00006842-199207000-00010
|View full text |Cite
|
Sign up to set email alerts
|

“Person under train” incidents: medical consequences for subway drivers.

Abstract: The PUT group had significantly more sick days during the interval from the event to 3 weeks later. During the period 3 weeks to 3 months after the event no difference between the groups was observed. From 3 months to 1 year after the PUT significantly more days were again reported by the PUT group. Thirty-eight percent in the PUT group versus 14% in the control group had at least 1 month of sickness absence during this period. A mild acute psychophysiological reaction was observed 3 weeks after the event, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
5

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 4 publications
0
27
0
5
Order By: Relevance
“…These factors were confirmed both with respect to 1 year-and lifetime prevalence. Also with regard to just the occurrence and duration of sick leave, the impact of the severity of third party injuries as well as the severity of the accident itself was confirmed (Theorell et al 1992(Theorell et al , 1994. Both studies showed that the effects for the affected driver both with respect to PTSD and sick leave were more severe with a third party injury being grave as compared to it being nonexistent, light (Theorell et al 1994), or lethal (ebda; Theorell et al 1992;Kim et al 2013).…”
Section: Risk and Prognostic Factors For Posttraumatic Diseasesmentioning
confidence: 86%
See 1 more Smart Citation
“…These factors were confirmed both with respect to 1 year-and lifetime prevalence. Also with regard to just the occurrence and duration of sick leave, the impact of the severity of third party injuries as well as the severity of the accident itself was confirmed (Theorell et al 1992(Theorell et al , 1994. Both studies showed that the effects for the affected driver both with respect to PTSD and sick leave were more severe with a third party injury being grave as compared to it being nonexistent, light (Theorell et al 1994), or lethal (ebda; Theorell et al 1992;Kim et al 2013).…”
Section: Risk and Prognostic Factors For Posttraumatic Diseasesmentioning
confidence: 86%
“…resulting in severe bodily harm or death (Theorell et al 1992;Vatshelle and Moen 1997;Weiss and Farrell 2006).…”
mentioning
confidence: 99%
“…Theorell et al (70) very recently reported that the subway drivers who, subsequent to a "person under train" incident, experienced the highest level of depression and had a need for longterm sick leave showed high plasma cortisol levels. This finding is congruent with those showing that the cortisol excretion rate is directly proportional to the level of distress (71).…”
Section: Catecholamines and Corticosteroidsmentioning
confidence: 99%
“…For in stance. studies have shown that plasma corti sol and prolactin increase during unemploy ment [14], Plasma prolactin increases during the weeks after a subway train driver has killed or seriously injured somebody under the train [15]. Plasma cortisol increases dur ing the terminal phase of the cancer illness of a close relative [16,17], Cellular immune function is affected by the death of a spouse [18] and by unemployment.…”
Section: Physiological Monitoringmentioning
confidence: 99%
“…Another example is the study of subway drivers who had experienced a person under train (PUT) incident [15]. Three weeks after the PUT incident, a significantly increased sleep disturbance score and elevated plasma prolactin was observed.…”
Section: Theorellmentioning
confidence: 99%